2015
DOI: 10.1371/journal.pone.0117666
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MRI-Based Study in Patients with SPG4 Mutations

Abstract: Mutations in the SPG4 gene (SPG4-HSP) are the most frequent cause of hereditary spastic paraplegia, but the extent of the neurodegeneration related to the disease is not yet known. Therefore, our objective is to identify regions of the central nervous system damaged in patients with SPG4-HSP using a multi-modal neuroimaging approach. In addition, we aimed to identify possible clinical correlates of such damage. Eleven patients (mean age 46.0 ± 15.0 years, 8 men) with molecular confirmation of hereditary spasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 30 publications
4
43
1
Order By: Relevance
“…Our findings are consistent with those of Faber et al (26), who found decreased cortical thickness in the precentral and paracentral motor cortices, superior parietal cortices, superior temporal gyrus, and cingulate cortices in SPG11-HSP, which suggests that SPG4-HSP and SPG11-HSP have similar cortical mechanisms. However, Rezende et al (15) did not find cortical thinning in SPG4-HSP on FreeSurfer analysis. This difference in the results of their study and our study may be attributable to the fact that our patients were recruited from a family.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with those of Faber et al (26), who found decreased cortical thickness in the precentral and paracentral motor cortices, superior parietal cortices, superior temporal gyrus, and cingulate cortices in SPG11-HSP, which suggests that SPG4-HSP and SPG11-HSP have similar cortical mechanisms. However, Rezende et al (15) did not find cortical thinning in SPG4-HSP on FreeSurfer analysis. This difference in the results of their study and our study may be attributable to the fact that our patients were recruited from a family.…”
Section: Discussionmentioning
confidence: 91%
“…It is linked to abnormal brain function in terms of the cerebral blood flow (9), neuronal biochemistry (10), cortical sensorimotor function (11), and resting-state neuronal activity (12). Moreover, damage has been found in brain structures in the white matter, including the corticospinal tracts, cingulum, cerebral pedicle, internal capsule, cerebellum, and corpus callosum (3,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In the complicated form, there is widespread grey matteratrophy, particularly at the basal ganglia, which explains the more heterogeneous phenotype that frequently includes parkinsonism and dystonia. [ 6 ] These findings in isolation are not useful in diagnosis but when present simultaneously along with spinal cord changes are highly suggestive of HSP. Additional reported findings include bilateral medial frontal atrophy, widening of interhemispheric fissure, and reduced size of thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Both authors showed correlations between white matter tract disruption and disease severity, indicating that diffusion tensor imaging measures could be used as biomarkers. Rezende and colleagues also demonstrated the absence of cortical thinning as a hallmark of this pure subtype of HSP 44,45 . Regarding HSP-SPG11, both França et al 46 and Pan et al 47 revealed widespread white matter microstructural disruption.…”
mentioning
confidence: 92%
“…They demonstrated that microstructural brain abnormalities are rather diffuse and not restricted to motor pathways, when one analyzes multiple subtypes of HSP. Lindig 44 and Rezende 45 , both in 2015, made substantial contributions to the delineation of the extent of neurodegeneration specifically associated with HSP-SPG4. Both authors showed correlations between white matter tract disruption and disease severity, indicating that diffusion tensor imaging measures could be used as biomarkers.…”
mentioning
confidence: 99%